Semantic Issues of OCL: Past, Present, and Future - Brucker, Achim; Doser, Jürgen; Wolff, Burkhart (Electronic Communications of the EASST, 2007)
We report on the results of a long-term project to formalize the semantics of OCL 2.0 in Higher-order Logic (HOL). The ultimate goal of the project is to provide a formalized, machine-checked semantic basis for a theorem proving environment for OCL (as an example for an object-oriented specification formalism) which is as faithful as possible to the original informal semantics. We report on various (minor) inconsistencies of the OCL semantics, discuss the more recent attempt to align the OCL semantics with UML 2.0 and suggest several extensions which make, in our view, OCL semantics more fit for future extensions towards program verifications and specification refinement.